Pengaruh Penggunaan E-LKPD Berbasis Pendekatan Investigasi Terhadap Kemampuan Berpikir Kritis Siswa Kelas 5 Pada Mata Pelajaran Matematika: E-LKPD, Kemampuan Berpikir Kritis, Matematika SD, Pendekatan Investigasi. - Nafia Wafiqni; Shafa Nabilah (Al-Aulad: Journal of Islamic Primary Education, 2026)
This study aims to determine the effect of the use of E-LKPD based on an investigation approach on the critical thinking skills of 5th grade students at MI Pembangunan UIN Jakarta in mathematics. The research method used is Pre Experimental Design. The research design used is One Group Pretest-Posttest Design. The research instrument used is 10 essay questions that have been tested for validity and reliability. The data collection technique used is a test in the form of descriptive questions and documentation. The data analysis technique used in this study uses the normality test with the Shapiro Wilk technique. Furthermore, the homogeneity test uses One Way ANOVA. Then the hypothesis test uses the Paired  Sample T-test with a significance level of 5%. The average pretest score is 33.24 and the posttest is 41.52. The average N-Gain Score is 49% and is included in the "Medium" category. The results of this study indicate that there is an effect of the use of E-LKPD based on an investigation approach on the critical thinking skills of 5th grade students of MI Pembangunan UIN Jakarta in mathematics. This can be proven by the results of the t-test on the average post-test score, which obtained a p < 0.05, meaning that H0 is rejected and Ha is accepted.